Risk Starvation Contributes to Dementias and Depressions: Whiffs of Danger Are the Antidote - Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
This paper's objective is to use SKAT, the author's Stages of Knowledge Ahead Theory of risk, to shed fresh light on the treatment and prevention of mental disorders. SKAT employs a broad definition of risk that allows for nice – not merely nasty – possibilities. SKAT is here shown to solve eight epidemiological puzzles left unexplained by our current theories and associated treatments for the demented and depressed. SKAT does so by enabling a decision model of mental health that puts centre stage why people (and other soft-wired animals) have brains – to make decisions under risk. To make good decisions (be healthy), brains need exercise. Brains get beneficial exercise from what the paper terms “whiffs of danger”, namely sets of risks with the characteristics that the risks are 1) tiny, 2) varied, and 3) frequent. Brains deteriorate when there are shortfalls in such risk exercise. The paper terms such shortfalls “risk starvation”. Those lacking a history of whiffs find normal mishaps too stressful and frequently become depressed. A lot of time with an inadequate amount of whiffs generates the endemic co-morbidity of becoming demented as well as depressed. Socio-economic cultural changes such as the introduction of unemployment benefits and old age pensions and increasing protection of women and children have had the beneficial effects of removing big challenges and big dangers and thus of prolonging physical longevity. But these changes also removed the tiny challenges and tiny dangers formerly faced by those sub-groups in the population identified as more prone to depressions and dementias. Unintentionally, these sub-groups thus were deprived of whiffs of danger, and suffered from risk starvation. In both drug and psychotherapeutic stress research and treatments of the depressed and demented, there should be injections of whiffs of danger to enhance the likelihood of enduring improvements. It is unkind and dangerous for people's brains to be treated with drugs while maintaining the modern socioeconomic culture of coddling parents and coddling college / university student counsellors, coddling unemployment benefits and coddling old age pensions. These coddles need to be complemented with whiffs of danger, tiny varied chances and challenges. These whiffs of danger need to be introduced in three forms: eliciting social security recipients' whiffs of danger in the form of little obligations to help the community; educating the poor and other sub-groups that believe closeting females at home endangers their mental health; and educating parents on the damage from overprotection. Overprotection prevents children from becoming inoculated against depression with sensible hope developed over a childhood in which they were allowed to experience numerous failures, not merely numerous successes from parents too closely engineering their environment. Research is required on the likely role of risk starvation in mental disorders other than dementias and depressions and in some physical illnesses.
Keywords: 330; stress; whiffs of danger; decision; dementia; depression; risk starvation; risk; learning; hope; fear; risk-based emotions; Psychische Störung; Risikopräferenz; Emotion; Lernprozess